2002
DOI: 10.1071/ar01133
|View full text |Cite
|
Sign up to set email alerts
|

Matching physiological traits and ion concentrations associated with salt stress in cowpea genotypes

Abstract: The salt tolerance of 25 cowpea genotypes (Vigna unguiculata L. Walp.) was studied during early vegetative growth. Salinity treatments were applied by irrigating with a nutrient solution containing 0, 85, and 170 mmol NaCl/L. Seedling survival decreased linearly as salinity increased, but this enabled cowpea genotypes to be ranked for salinity tolerance according to the magnitudes of slopes of regression of survival percentage on salinity. Sodium concentration was higher in roots than in shoots in all genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
2
5
2
Order By: Relevance
“…Some mechanisms, such as reduced Na + delivery to the shoot, tissue‐ and organ‐specific Na + compartmentation and recirculation of Na + from the leaves back to the roots (Shabala and Cuin 2008) may be involved in this response. In any case, no evidence that salt tolerance in cowpea is related to differences in Cl − accumulation was found, contrary to what was previously documented by Murillo‐Amador et al. (2002b, 2006a).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Some mechanisms, such as reduced Na + delivery to the shoot, tissue‐ and organ‐specific Na + compartmentation and recirculation of Na + from the leaves back to the roots (Shabala and Cuin 2008) may be involved in this response. In any case, no evidence that salt tolerance in cowpea is related to differences in Cl − accumulation was found, contrary to what was previously documented by Murillo‐Amador et al. (2002b, 2006a).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we analysed the effects of moderate (non‐lethal) external salinity on growth and photosynthesis during the vegetative stage of two contrasting cowpea cultivars. Our results showed that improved salt tolerance may be primarily associated with restricted Na + accumulation in leaves, as had already been reported for cowpea (Murillo‐Amador et al. 2002b, Costa et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although Murillo-Amadot et al (2002) found that the chlorophyll content of salt-tolerant cowpea genotypes increased under salt stress, the chlorophyll content of M. sinensis decreased with increasing NaCl concentration and stress duration in the present study. This effect may be due to inhibition of chlorophyll synthesis or acceleration of its degradation as a result of salinity (Netondo et al, 2004b;Zhao et al, 2007).…”
Section: Discussioncontrasting
confidence: 91%
“…However, in contrast to other crops, scant information is available on its basic physiological processes involved in salt tolerance. Cowpea cultivars showing contrasting responses to salinity have been identified (Murillo-Amador et al 2002;Costa et al 2003;Murillo-Amador et al 2006); more recently, we suggested that salt tolerance could be associated with restricted Na ? accumulation in leaves, improved leaf area and increased photosynthetic rates per unit leaf mass in cowpea (Praxedes et al 2010).…”
Section: Introductionmentioning
confidence: 97%